Application of The OPERA Information System in Hotel Reservations to Increase The Productivity of The Front Office Department (Case Study at the Grand Hyatt Hotel Bali) - Wirya, I Made Suwitra; Widiantara, I Gusti Agung Bagus; Darma Susila, I Made Gede (Jurnal Manajemen Pelayanan Hotel, 2023)
Application of Information Systems OPERA at Reservations Section, Front Office Department, in Hotel GrandHyatt Bali. The information system is a system within an hotel that reconciles the needs of daily transactionprocessing, support the operation, managerial in character and strategic activities of an hotel as well as providecertain outside parties with the necessary reports. In general, the reservation section in front office departmentis reserving facilities including accommodation, food and beverage, seat pad in the show, airplanes, trains, bus,entertainment, night club, discoutegue including booking hotel rooms. Population and sample in this researchwere employees on duty in the reservation section, front office department who really understands the OPERAinformation system being researched at this time, the respondents are 11 people. The calculation is done byusing the simple empirical formula, as well as the determination of the value-oriented to simple statistics withdata collected through a questionnaire. Motivation of development of information systems at Grand Hyatt BaliHotel is a profit motive, thus the profit and loss aspects are taken into consideration in the development of thesystem. Based on respondents’ ratings of the three operational criteria of reservation section in front officedepartment in Grand Hyatt Bali Hotel. In general the condition of reservation section based on the views ofrespondents is 87.37% agree 12:12% fairly agree and 0.50% disegree, and there are some advantages of usingthe OPERA information system are speed, convenience and other benefits.Keywords: Application, Information System, Reservation, Front Office